2014
DOI: 10.3389/fmicb.2014.00196
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prokaryotic community structure from Mediterranean and Atlantic saltern concentrator ponds by a metagenomic approach

Abstract: We analyzed the prokaryotic community structure of a saltern pond with 21% total salts located in Isla Cristina, Huelva, Southwest Spain, close to the Atlantic ocean coast. For this purpose, we constructed a metagenome (designated as IC21) obtained by pyrosequencing consisting of 486 Mb with an average read length of 397 bp and compared it with other metagenomic datasets obtained from ponds with 19, 33, and 37% total salts acquired from Santa Pola marine saltern, located in Alicante, East Spain, on the Mediter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 68 publications
10
63
0
Order By: Relevance
“…The Santa Pola and Isla Cristina metagenomes have previously been taxonomically profiled through mapping of reads to 16S rRNAs obtained from the Ribosomal Database Project (Fernandez et al, 2013; Fernández et al, 2014b; Ventosa et al, 2014). These 16S rRNA profiling studies revealed that the lowest salinity saltern (SS13) contained a community of bacterial Actinobacteria and Proteobacteria and archaeal Euryarchaeota, while members of the Euryarchaeota increased in abundance with increasing salinity (Fernández et al, 2014c; Fernández et al, 2014a; Ventosa et al, 2015). Compared with the Santa Pola salterns, Cahuil and Isla Cristina salterns may be more dynamic, with more rapidly changing daily and yearly temperatures and higher rainfall (Fernández et al, 2014c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Santa Pola and Isla Cristina metagenomes have previously been taxonomically profiled through mapping of reads to 16S rRNAs obtained from the Ribosomal Database Project (Fernandez et al, 2013; Fernández et al, 2014b; Ventosa et al, 2014). These 16S rRNA profiling studies revealed that the lowest salinity saltern (SS13) contained a community of bacterial Actinobacteria and Proteobacteria and archaeal Euryarchaeota, while members of the Euryarchaeota increased in abundance with increasing salinity (Fernández et al, 2014c; Fernández et al, 2014a; Ventosa et al, 2015). Compared with the Santa Pola salterns, Cahuil and Isla Cristina salterns may be more dynamic, with more rapidly changing daily and yearly temperatures and higher rainfall (Fernández et al, 2014c).…”
Section: Resultsmentioning
confidence: 99%
“…Technical details about these microbial metagenomes are provided in Table 1. Further details about sampling are described in associated publications (Ghai et al, 2011; Fernandez et al, 2013; Fernández et al, 2014b; Fernández et al, 2014c; Plominsky et al, 2014). Chula Vista microbial metagenomes were obtained from the iMicrobe Collaborative (Hurwitz, 2014) and have been previously examined in a larger study of several aquatic biomes (Rodriguez-Brito et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the community structure of an intermediate salinity pond (21% NaCl) located in southern Spain on the Atlantic shore was more similar at higher taxonomic levels to the Mediterranean 33% NaCl, rather than the expected 19% NaCl pond ( Figure 1). However, differences at genus level were detected between those ponds indicating that community structure is not based exclusively on salt concentrations or geographic proximity [23].…”
Section: Introductionmentioning
confidence: 92%
“…The most abundant bacterial genera thriving in such environments, as revealed by both culture-dependent and -independent methods, were Salinibacter and Salicola [5,33]. In general, diversity studies have been performed mostly in brines [5,15,20,34], with very few in corresponding sediments [29].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the current studies on the diversity of halophilic microorganisms in hypersaline systems have been performed by means of culture-independent molecular techniques, such as, for example, on either 16S rRNA gene diversity [20] or by metagenomic approaches [15]. Despite the fact that molecular studies describe to a great extent the taxonomic and genetic diversity of the key players in their environments, they have failed to culture living organisms that can be potentially important sources of information for biotechnological, pharmaceutical and even taxonomic purposes.…”
Section: Introductionmentioning
confidence: 99%